PORTUGUS (CIPEEX, 2022)
THIS SUMMARY PROPOSES TO DEMONSTRATE THE RELATIONSHIP BETWEEN THE CONSTITUTION OF AN ETHICAL SUBJECT AND QUALITY EDUCATION. SPECIFICALLY, DISCIPLINES CHARACTERIZED BY CRITICAL, COMPLEX AND CONTEXTUAL CONTENT. THROUGH A MULTIDISCIPLINARY BIBLIOGRAPHIC RESEARCH, IT WAS POSSIBLE TO SEW A LINE OF REASONING THAT LINKS A HUMANE AND QUALITY SCHOOL, TEACHING WITH CRITICAL KNOWLEDGE, AND ETHICAL DEVELOPMENT.